Additional Usefulness of Bronchoscopy in Patients with Initial Microbiologically Negative Pulmonary Tuberculosis: A Retrospective Analysis of a Korean Nationwide Prospective Cohort Study - Oh JY; Lee SS; Kim HW; Min J; Ko Y; Koo HK; Jeong YJ; Kang HH; Kang JY; Kim JS; Park JS; Kwon Y; et al. (Infection and Drug Resistance, 2022)
Jee Youn Oh,1 Sung-Soon Lee,2 Hyung Woo Kim,3 Jinsoo Min,4 Yousang Ko,5 Hyeon-Kyoung Koo,2 Yun-Jeong Jeong,6 Hyeon Hui Kang,7 Ji Young Kang,8 Ju Sang Kim,3 Jae Seuk Park,9 Yunhyung Kwon,10 Jiyeon Yang,10 Jiyeon Han,10 You Jin Jang,10 Min Ki Lee,11 Yangjin Jegal,12 Young-Chul Kim,13 Yun Seong Kim14 1Division of Pulmonary, Allergy, and Critical Care Medicine, Department of Internal Medicine, Korea University Guro Hospital, Korea University College of Medicine, Seoul, Republic of Korea; 2Division of Pulmonary and Critical Care Medicine, Department of Internal Medicine, Inje University Ilsan Paik Hospital, Inje University College of Medicine, Goyang, Republic of Korea; 3Division of Pulmonary and Critical Care Medicine, Department of Internal Medicine, Incheon St. Mary’s Hospital, College of Medicine, The Catholic University of Korea, Seoul, Republic of Korea; 4Division of Pulmonary and Critical Care Medicine, Department of Internal Medicine, Daejeon St. Mary’s Hospital, College of Medicine, The Catholic University of Korea, Seoul, Republic of Korea; 5Division of Pulmonary, Allergy and Critical Care Medicine, Department of Internal Medicine, Kangdong Sacred Heart Hospital, Hallym University College of Medicine, Seoul, Republic of Korea; 6Division of Pulmonary and Critical Care Medicine, Department of Internal Medicine, Dongguk University Ilsan Hospital, Goyang, Republic of Korea; 7Division of Pulmonary, Critical Care and Sleep Medicine, Department of Internal Medicine, Ulsan University Hospital, University of Ulsan College of Medicine, Ulsan, Republic of Korea; 8Division of Pulmonary and Critical Care Medicine, Department of Internal Medicine, Seoul St. Mary’s Hospital, College of Medicine, The Catholic University of Korea, Seoul, Republic of Korea; 9Division of Pulmonary Medicine, Department of Internal Medicine, Dankook University College of Medicine, Cheonan, Republic of Korea; 10Division of Tuberculosis Prevention and Control, Korea Disease Control and Prevention Agency, Cheongju, Republic of Korea; 11Department of Internal Medicine, Pusan National University Hospital, Pusan National University School of Medicine, Pusan, Republic of Korea; 12Division of Pulmonary, Critical Care and Sleep Medicine, Department of Internal Medicine, Ulsan University Hospital, Ulsan University College of Medicine, Ulsan, Republic of Korea; 13Division of Pulmonary and Critical Care Medicine, Department of Internal Medicine, Chonnam National University Hwasun Hospital, Chonnam National University Medical School, Hwasun, Republic of Korea; 14Department of Internal Medicine, Pusan National University Yangsan Hospital, Pusan National University School of Medicine, Yangsan, Republic of KoreaCorrespondence: Sung-Soon Lee, Division of Pulmonary and Critical Care Medicine, Department of Internal Medicine, Inje University Ilsan Paik Hospital, Inje University College of Medicine, Goyang, Republic of Korea, Tel +82-10-7173-6575, Fax +82-2-2626-1166, Email sungsoonlee@gmail.comPurpose: Bronchoscopy is widely used for microbiological diagnosis of patients with minimal sputum production. However, the usefulness of bronchoscopy in patient groups who benefit from subsequent microbiological confirmation has not been established.Patients and Methods: We retrospectively analyzed Korean tuberculosis (TB) cohort data from September 2018 to October 2019 to evaluate the usefulness of bronchoscopy in patients with microbiologically negative pulmonary TB (based on initial sputum polymerase chain reaction and culture results). The primary outcome was the proportion of microbiological diagnoses made after bronchoscopy. Secondary outcomes were the predictors of microbiological confirmation and the percentage of additional resistance detection after bronchoscopy.Results: A total of 5194 patients were diagnosed with pulmonary TB, 937 of whom were microbiologically negative for pulmonary TB based on the initial sputum findings. Of these, 319 patients underwent bronchoscopy, and further microbiological confirmation was achieved in 157 (49.1%) patients. The predictors of microbiological confirmation after bronchoscopy were age > 65 years, female sex, and low body mass index (BMI). The rate of additional resistance detection was 10.5% (multidrug resistant/rifampin-resistant 3.8%; isoniazid-resistant 5.7%).Conclusion: Bronchoscopy can be used for the detection of resistant pathogens. Bronchoscopy should be considered for microbiologically negative pulmonary TB in women aged > 65 years and with low BMI for subsequent microbiological confirmation.Keywords: tuberculosis, pulmonary, bronchoscopy, cohort studies